Bioactive Compounds in Standardized Atine Extracts: Anticancer and Immunomodulatory Properties – A Systematic Review and Meta-Analysis - Bombushkar, Igor; Gozhenko, Anatoliy; Zukow, Walery (Journal of Education, Health and Sport, 2025)
Background: Natural products remain a crucial source for anticancer and immunomodulatory therapy development. Standardized Atine extracts, containing defined bioactive compounds, show promising therapeutic potential, but systematic efficacy evaluation is lacking. Objective: To comprehensively evaluate the anticancer and immunomodulatory properties of standardized Atine extracts and their main components through systematic review and meta-analysis. Methods: Systematic search was conducted in PubMed, Embase, Cochrane Library, Web of Science, and SCOPUS (January 2000 – July 2025) according to PRISMA 2020 guidelines. Studies assessing the bioactivity of key Atine extract components were included: isoalantolactone, osthole, asarone, α-linolenic acid, and furfural derivatives. Random-effects models were used for meta-analysis. Results: A total of 23 studies met the inclusion criteria, encompassing 4,345 participants across in vitro, animal, and clinical studies. The meta-analysis revealed significant cytotoxic activity with pooled IC₅₀ values of 18.4 μM (95% CI: 15.2–21.6; I² = 34%). Animal studies demonstrated a 52.3% reduction in tumor volume (95% CI: 48.7–55.9%; I² = 39%). Clinical studies indicated improved overall survival (HR = 0.73; 95% CI: 0.62–0.86; I² = 28%). Immunomodulatory effects included a 38.2% increase in NK cell activity (95% CI: 34.1–42.3%; I² = 31%) and significant cytokine modulation. Conclusions: Standardized Atine extracts demonstrate significant anticancer and immunomodulatory potential through multitarget mechanisms. Well-designed clinical trials are needed to validate preclinical findings.